PEMETAAN SOSIAL EKOWISATA BERKELANJUTAN: TINJAUAN ACTION NETWORK THEORY - Maya Atri Komalasari; Rosiady Husaenie Sayuti; Azhari Evendi; Lalu Hendra Wirawan; Rosiady Lalu Gigih Izzul Islam; Sibyanula Prisetyatna (LPSDI Bina Patria, 2025)
Social mapping is very important before the implementation of programs. Unfortunately, not all programs in their planning include aspects of social mapping, such as ecotourism development programs. West Sekotong Village has potential in ecotourism development but has not immediately focused on directing it. This study aims to conduct social mapping in the development of ecotourism in West Sekotong Village with a review of Action Network Theory. Research using the Rapid Rural Appraisal (RRA) method with purposive techniques to determine informants. Data collection techniques use interviews, observations, documentation and questionnaires. Analyze the data with interactive model. The results of the study show that the existence of a complex ecotourism development network consists of various important aspects, including: 1). Ecotourism category, 2). Actors, 3). Resources and 4). Interaction between actors. The actors involved in the network are not only human actors, but also non-human actors such as nature and technology These non-human actors have an equal role to other actors because of the resources they have and the interactions they have with other actors. This research is expected to enrich the collection of knowledge related to social mapping of ecotourism with the Action Network Theory approach.